2021
DOI: 10.1186/s12885-021-08010-4
|View full text |Cite
|
Sign up to set email alerts
|

Is stress related to the presence and persistence of oncogenic human papillomavirus infection in young women?

Abstract: Background Persistent infection with high-risk human papillomavirus (HR-HPV) is the most important risk factor for the development of cervical cancer, but factors contributing to HR-HPV persistence are incompletely understood. The objective of this study was to test for associations of chronic stress and two aspects of diurnal cortisol secretion (i.e., the cortisol awakening response [CAR] and total cortisol output over the day [AUCgday]) with HR-HPV status at baseline and 12 months later (foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Indeed, a seminal study in healthy women demonstrated that in vitro stimulation with HPV16 virus-like particles combined with an exogenous administration of oestradiol and progesterone decreased lympho-proliferation and pro-inflammatory cytokine production while increasing anti-inflammatory cytokines and transcriptional regulators of regulatory T cells [ 13 ]. This notion echoes the results of a previous report by our group, which found that chronic stress and the stress hormone cortisol, an important modulator of immune responses, were linked to HR-HPV status at baseline and follow-up [ 8 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Indeed, a seminal study in healthy women demonstrated that in vitro stimulation with HPV16 virus-like particles combined with an exogenous administration of oestradiol and progesterone decreased lympho-proliferation and pro-inflammatory cytokine production while increasing anti-inflammatory cytokines and transcriptional regulators of regulatory T cells [ 13 ]. This notion echoes the results of a previous report by our group, which found that chronic stress and the stress hormone cortisol, an important modulator of immune responses, were linked to HR-HPV status at baseline and follow-up [ 8 ].…”
Section: Discussionsupporting
confidence: 90%
“…This study was part of a larger study examining the influence of psychobiological factors on the course of HR-HPV (see [ 8 ] for a participant flow chart). For its main analyses, a power analyses yielded a sample size of N = 90 participants to detect medium-sized effects (see [ 8 ]).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies do not refer to a relationship between adverse life events such as divorce, the death of a close relative, or lack of social support and the risk of developing CxCa precursor lesions [61,62]. Nevertheless, other researchers have shown an association between psychosocial stress, cortisol levels, and the risk of HR-HPV infection, suggesting that this hormone may be related to cervical carcinogenesis [63,64]. Moreover, systemic use of glucocorticoids could increase the risk for HR-HPV persistence (OR, 2.04; 95% CI, 1.16-3.56) [65].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic psychological stress can affect the durability of HPV clinical symptoms and contribute to the progress of HPV-related cervical cancer. Furthermore, a large number of studies have reported that there is a relationship between psychological stress and the prevalence and progress of this virus in relation to cervical dysplasia and cancer (19,20). People with a positive high-risk HPV test have been shown to have signi cantly higher cortisol levels compared with those with a negative test, and chronic stress and daily cortisol are associated with HPV infection.…”
Section: Introductionmentioning
confidence: 99%